Tourism in the Muslim world - Scott, Noel, 1958-; Jafari, Jafar (Bridging tourism theory and practice ;, 2010)
"Tourism in the Muslim World provides a synthesis of thought on an influential current issue for tourism and indeed for our times, and a point of focus for tourism researchers, managers and developers in countries such as the United Arab Emirates, Jordan, Egypt, Maldives and Turkey, as well as the Western world, eager to increase their share in this 1.5 billion strong tourist market. Its chapters raise conceptual, practical, and thought-provoking issues for the wider tourism community as it deals with the growth of new markets and destinations in a globalized economy. This collection of culturally and geographically diverse papers feature both Muslim and non-Muslim (country) insights on this international theme. It draws on contributions from a variety of disciplinary perspectives such as law, theology, business, tourism development, sociology, anthropology, and more. Tourism in the Muslim World is the second title in Emerald's new book series Bridging Tourism Theory and Practice and will appeal to researchers and research students in the social science and management disciplines, as well as to tourism and hospitality professionals with an interest in the Muslim market."